(untitled) (Scientific journal of the Fergana State University, 2024)
The article presents information about the cognitive competence of music education teachers, their ability to obtain information in the educational process, organize their activities in educational systems, and provide themselves with new information. In this process of music education, it was suggested that the cognitive psychology of students should be improved through effective pedagogical approaches in order to regularly update their professional knowledge, gradually develop skills, and subsequently teach as music education. teachers, solve problems in their imaginary thinking. Music education also plays an important role in social and personal development. Cognitive competence is important in this topic, and competence ensures that students can easily acquire new knowledge from teachers. The article is devoted to these topical issues.